2019
DOI: 10.1103/physrevfluids.4.063902
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of vortex pairing and mixing to initial perturbations in stratified shear flows

Abstract: The effects of different initial perturbations on the evolution of stratified shear flows that are subject to Kelvin-Helmholtz instability and vortex pairing have been investigated through Direct Numerical Simulation (DNS). The effects of purely random perturbations of the background flow are sensitive to the phase of the subharmonic component of the perturbation that has a wavelength double that of the Kelvin-Helmholtz instability. If the phase relationship between the Kelvin-Helmholtz mode and its subharmoni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 54 publications
(100 reference statements)
3
20
0
Order By: Relevance
“…Therefore, it is difficult to differentiate LCVI from SVBI without performing the stability analysis. Furthermore, the growth of secondary instabilities is highly sensitive to the initial broadband velocity fluctuations (Dong et al 2019). We have simulated the Ri = 0.16 case with two different choices for the initial velocity perturbations: one where the energy spectrum peaks at k 0 = 1.13 and another with a peak at k 0 = 1.24.…”
Section: Routes To Turbulence: K-h Shear Instability and Secondary Inmentioning
confidence: 99%
“…Therefore, it is difficult to differentiate LCVI from SVBI without performing the stability analysis. Furthermore, the growth of secondary instabilities is highly sensitive to the initial broadband velocity fluctuations (Dong et al 2019). We have simulated the Ri = 0.16 case with two different choices for the initial velocity perturbations: one where the energy spectrum peaks at k 0 = 1.13 and another with a peak at k 0 = 1.24.…”
Section: Routes To Turbulence: K-h Shear Instability and Secondary Inmentioning
confidence: 99%
“…This shows that w β has the same phase as η β provided Ω β is purely imaginary (unstable flow with zero phase speed). The classic dispersion relation for KH instability under the Boussinesq approximation yields (Drazin & Reid 2004),…”
Section: Problem Layoutmentioning
confidence: 99%
“…Experiments (Ho & Huang 1982; Husain & Hussain 1995), numerical simulations (Patnaik, Sherman & Corcos 1976; Corcos & Sherman 1984; Dong et al. 2019) and theoretical models (Kelly 1967; Nikitopoulos & Liu 1987) on vortex pairing have revealed that, depending on the phase difference (between the primary KH and the first subharmonic component), the outcome in the nonlinear stages can be radically different. An optimal phase difference leads to a ‘rolling interaction’ of vortices, while ‘shredding interaction’ occurs at a non-optimal value of phase difference.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations